(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic has left a huge impact on various business actors, especially for micro, small, and medium enterprises (MSMEs) who are engaged in the culinary sector in the form of food and beverages. Seeing the development of digital platforms and the Covid-19 pandemic which is starting to subside, direct marketing or through online platforms still requires a marketing strategy. Various marketing strategies such as market segmentation are the marketing processes taken to attract consumer purchasing power. A descriptive qualitative approach is used in the service in the form of training in analysis and market segmentation of culinary businesses in the digital era after the Covid-19 pandemic which aims to describe the relationship between attitudes, activities, and processes that are currently taking place. Based on the characteristics of the consumer segments studied, it can be seen that the female gender has a high percentage of 46.67% compared to men. In addition, the school age range of 40% is the largest consumer. This can be a reference for choosing the right superior product for the market.